Analysis of Hormonal and Metabolic Parameters In Hypothyroidism, Subclinical Hypothyroidism and Pcos - Iftikhar, Maleeha; Qureshi, Muhammad Naeem; Hassan, Fayyaz; Siddiqi, Fuad Ahmad; Khan, Imran; Yaseen, Laila (Pakistan Armed Forces Medical Journal, 2025)
Objective: To analyze the hormonal and metabolic parameters in subclinical hypothyroidism, hypothyroidism, and Polycystic Ovary Syndrome (PCOS) among women of reproductive age.Study Design: Cross-sectional study.Place and Duration of Study: Combined Military Hospital (CMH), Rawalpindi, Pakistan, from Jan 2024 to Dec 2024.Methodology: Total 114 participants were enrolled and their blood samples analyzed by dividing into three groups: hypothyroidism without PCOS, subclinical hypothyroidism without PCOS, and PCOS. Blood samples were drawn into gel tubes and centrifuged at 3000 RPM for 5 minutes. The serum was then analyzed using chemiluminescence immunoassay to measure hormonal and metabolic parameters of women of reproductive age. A standardized proforma was used to collect data on demographics, clinical history, and biochemical evaluations.Results: A total of 114 participants were included in this study. A significant difference was observed in serum follicle stimulating hormones (FSH) level across the group (p=0.007). However, all the other parameters showed no significant difference across the groups with p>0.05. For age and Body Mass Index (BMI), a weak negative correlation with thyroid stimulating hormone (TSH) and FSH, respectively was statistically significant while other hormones showed no significant correlation with age and BMI (p>0.05).Conclusion: TSH level showed statistically significant difference among females with hypothyroidism, sub-clinical hypothyroidism and PCOS while other hormonal parameters showed no statistically significant difference among groups.